Crisis del espacio teatral en Lima a partir de una revisión histórica del teatro occidental - Mesta León, Carlos Guillermo (2025)
In the present work, the relationship between stage space and theatrical architecture throughout the history of Western theater is analyzed, with emphasis on the crisis of theatrical space in Lima, Peru. The objective is to highlight how theatrical architecture emerges from the interaction between text, actors, and audience. For this purpose, a methodology based on a critical review of relevant literature and the analysis of significant cases in the evolution of theater is employed. The article addresses key concepts, such as the active participation of the audience in ancient Greek theater and the entertainment-oriented approach of Roman theater. Likewise, historical moments that marked the evolution of scenic space are examined, including the influence of the Church during the Middle Ages and the Renaissance, which freed theater from ecclesiastical constraints. The contributions of innovators such as Adolphe Appia and the Bauhaus movement are also analyzed, as they promoted three-dimensional theatrical architecture and the fusion of art and architecture. The findings indicate that, although theatrical architecture has evolved, frontal spaces predominate in Lima, limiting interaction. It is concluded that the theatrical act requires a physical space that allows for a dynamic connection between actors, text, and audience, and it is suggested that new architectural configurations could transform the theatrical experience in such a way that it adapts to contemporary demands.